Polioencephalomalacia in a lamb - Karapinar, Tolga; Dabak, Durrin Ozlem; Eroksuz, Yesari (My University, 2009)
Polioencephalomalacia was diagnosed in a lamb on the basis of clinical findings, increased thiamine pyrophosphate effect and confirmatory postmortem changes.